2011
DOI: 10.1258/ijsa.2009.009059
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol use and HIV sexual risk among MSM in Chennai, India

Abstract: Summary Men who have sex with men (MSM) in India are a core risk group for HIV. Heavy alcohol consumption is associated with increased sexual risk-taking behaviours in many cultures, in particular among MSM. However, no studies to date have explored alcohol use and HIV risk among MSM in India. MSM in Chennai, India (n = 210) completed an interviewer-administered behavioural and psychosocial assessment. Bivariate and multivariable logistic regression procedures examined behavioural and demographic associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
43
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 33 publications
7
43
1
Order By: Relevance
“…Condomless anal intercourse is particularly strongly correlated with alcohol use disorder (a clinical term determined by the Diagnostic and Statistical Manual of Mental Disorders) 42. This global-level association has been documented in many countries, including Australia,11 Cambodia,43 India,44 China,45 Canada46 and the USA 47. However, in many instances, interaction effects with illicit drugs or varied psychosocial factors that also influence sexual risk-taking can confound significant findings 37…”
Section: Impacts Of Substance Usementioning
confidence: 96%
“…Condomless anal intercourse is particularly strongly correlated with alcohol use disorder (a clinical term determined by the Diagnostic and Statistical Manual of Mental Disorders) 42. This global-level association has been documented in many countries, including Australia,11 Cambodia,43 India,44 China,45 Canada46 and the USA 47. However, in many instances, interaction effects with illicit drugs or varied psychosocial factors that also influence sexual risk-taking can confound significant findings 37…”
Section: Impacts Of Substance Usementioning
confidence: 96%
“…Using data from a study of MSM attending STI clinics in Mumbai and Hyderabad, Narayanan et al reported an HIV prevalence of 43.6% among MSM who engage in sex work (Narayanan et al, 2013). In Chennai – the biggest industrial and commercial center of South India – the prevalence of HIV and risk factors for HIV acquisition among the broader MSM community have been characterized (Chakrapani, Newman, & Shunmugam, 2008; Go et al, 2004; Mimiaga et al, 2011; Thomas et al, 2009). Thomas et al identified not having previously engaged in an HIV prevention program, having symptoms of clinical depression and lower self-efficacy as predictors for MSM engaging in unprotected anal intercourse, a key risk factor for testing positive for HIV (Thomas et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…2,17 Binge drinking and other patterns of heavy alcohol use are independently associated with a variety of high-risk behaviors in MSM, including unprotected anal sex, multiple partners, and having HIV-serodiscordant partners, [18][19][20][21][22][23][24][25][26][27][28] a link also observed among Black, Native American, and older MSM. [29][30][31] Binge drinking and heavy alcohol consumption are major causes of incident HIV infections in MSM. Binge alcohol use was independently associated with a greater than threefold increase in odds for new HIV diagnoses among MSM who had a previously (past 12 months) negative HIV test in a case-control study.…”
Section: Introductionmentioning
confidence: 99%